Anthropology in the public arena : historical to contemporary contexts in Britain - MacClancy, Jeremy (John Wiley & Sons Inc., 2013)
This articulate and authoritative survey of both the popular and academic trends in anthropology demonstrates the broad relevance of anthropological knowledge and argues for a more inclusive conception of the discipline that engages the public imagination. Demonstrates the evolving social contexts of British anthropological theory and practice from the mid-19th centuryHighlights the importance of popular anthropology in forming and sustaining the professional disciplineExplores the past and present cross-fertilization of anthropologists, scientists and prominent.